2013
DOI: 10.7220/2029-5820.12.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Įgalinimo samprata socialinių paslaugų kontekste

Abstract: Vytauto Didžiojo universitetas Straipsnyje nagrinėjamos galios ir įgalinimo sampratos bei jų raiška socialiniųįVADAS Įgalinimas (angl. empowerment) per kelerius metus tapo labai madingu terminu, vartojamu įvairiais viešosios erdvės ir profesiniais kontekstais. Ši sąvoka ypač dažna socialinės gerovės srities akademiniuose ir praktiniuose pranešimuose bei diskusijose. Masinį termino vartojimą galima apibūdinti aforizmu: "Įgalina visi, įgalina viską". Toks koncepto masiškumas tarsi "išplauna" jo turinį, kai nebėr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…The researchers [5] note that the situations of social work practice, where employees, in spite of good intentions, can inhibit their clients by suppressing their initiative. Another obstacle arises, when social workers do not feel empowered, they will not take the initiative to help the client "here and now" and are afraid to be accused by their managers or administration.…”
Section: Isolated and Limited By Directives The Reality Of Social Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers [5] note that the situations of social work practice, where employees, in spite of good intentions, can inhibit their clients by suppressing their initiative. Another obstacle arises, when social workers do not feel empowered, they will not take the initiative to help the client "here and now" and are afraid to be accused by their managers or administration.…”
Section: Isolated and Limited By Directives The Reality Of Social Workmentioning
confidence: 99%
“…What's more, it is likely to happen that the issues raised by a social worker label this person as "problem brewing" and unable to cope with one's work? [5]. The bureaucratic provision of social services implemented by social workers is characterized by the low involvement of service users / clients as equivalent partners in solving their own social problems and having little effect on what services they would need.…”
Section: Isolated and Limited By Directives The Reality Of Social Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that, although social services at person's home are given priority, in Lithuania, research on the subject has not been conducted. The analysis of scientific literature revealed that scholars have drawn a great deal of attention to the problem of the quality of services [11][12][13][14], the management of social services and the effectiveness of services and the problem of the cost reduction of services [2,[16][17][18], the expression of empowerment in the context of social services [19,20]. In the context of the aforementioned studies, the problem of social services at home, as one of the priority areas of change in social services system is highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reasonably the question arises: How much power do social workers and social pedagogues have in order to achieve changes (Ruškus, Mažeikienė, Naujanienė, Motiečienė, & Dvarionas, 2013)? Do the very social workers and social pedagogues feel empowered?…”
Section: Introductionmentioning
confidence: 99%